2018
DOI: 10.15761/crt.1000220
|View full text |Cite
|
Sign up to set email alerts
|

Improving informed consent in cardiology practice: How much we need to do

Abstract: Cardiology interventions remain to be complex and difficult to understand by the general people. Consent requirements have become gradually challenging in parallel to the rise of autonomy as a dominant principle in biomedical ethics in addition to the complexity of cardiology intervention. Studies showed that patients have suboptimal understanding of the procedural risks and benefits.Many novel elucidations have been offered to enhance informed consent, many of which have narrowed, although not eradicated, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In our study, patients reported that they did not usually understand, or remember, the information given to them and, although fewer in number, many cardiologists shared the same view. Poor levels of patient comprehension and recall about the risks and benefits of PCI treatment have been reported in other international studies dating back over 20 years; [11][12][13][14][15][16][17]23 our study adds an English perspective to these. There appears to have been limited progress in addressing this challenge, but the implementation of educational interventions and decision aids offers two approaches to improve patient knowledge and recall which will optimise the wider decision-making process that overlaps with PCI informed consent.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In our study, patients reported that they did not usually understand, or remember, the information given to them and, although fewer in number, many cardiologists shared the same view. Poor levels of patient comprehension and recall about the risks and benefits of PCI treatment have been reported in other international studies dating back over 20 years; [11][12][13][14][15][16][17]23 our study adds an English perspective to these. There appears to have been limited progress in addressing this challenge, but the implementation of educational interventions and decision aids offers two approaches to improve patient knowledge and recall which will optimise the wider decision-making process that overlaps with PCI informed consent.…”
Section: Discussionmentioning
confidence: 52%
“…11 This general lack of awareness among patients about alternative treatment options is evident across other international survey studies which report that discussions about alternative treatments are not fully explored with patients scheduled for coronary revascularisation. 23 This finding is also apparent in research focusing on non-cardiac elective procedures in which informed consent interactions tend to confirm a predetermined decision rather than facilitate supported decisionmaking. 24 A preference to choose angioplasty as the first-line treatment for stable coronary artery disease, rather than medical therapy, has been reported elsewhere.…”
Section: Discussionmentioning
confidence: 96%